O horror do capitalismo no Brasil: representações do preconceito de classe no filme "o animal cordial" - Teles, Hugo Daniel Melo (2022)
This dissertation investigated the representations of social conflicts in the Brazilian horror cinema, based on the analysis of the film "The Friendly Beast", directed by Gabriela Amaral Almeida The goal of the research was, mainly, how the film portrays the class conflicts and the damages capitalism has enacted on present day brazilian society, which is still marked by a crescent social inequality. Through a social and historical comprehension of horror and its representations in art, as well as the definition of horror and its effects on the human psych, the present dissertation aims to expose how the horror in the analysed film works as a way of criticizing brazilian society. Horror is a genre that brings with itself a relation with what is shocking, that rallies the subject, in a way that, when using the genre to the brazilian context, it shows how horrifying the worker oppression can be in the country, specially after the reforms conducted post-2016. The research has used classic and contemporary marxist authors, as well as newer social concepts like the ones by Byung Chul-Han (2015) and the concept of Homem Cordial by Sérgio Buarque de Holanda (2012), a central point for the analyzed film itself; the analysis followed on the guidelines defined by Aumont-Marie (2004), being descriptive about the analyzed scenes, as well as using frames and dialogs of the film to analyze upon. The analysis ended up on clarifying on how capitalism and its more fluid version, imposed by the neoliberalism, ends up demanding the total exploration of subjects, taking away their dignity and personal autonomy. Another point established on the analysis is how the structure of capital has consolidated itself on a specific way, in order to perpetuate a violent system, in which dominance is exerted by the bourgeoisie and held up by the ideology of blaming the middle and lower classes for the problems of the country.